Financial Benefits of a Hepatopancreaticobiliary Program. Issue 5 (May 2016) - Rosemurgy, Alexander S.; Ryan, Carrie E.; Klein, Richard L.; Wood, Thomas W.; Co, Franka; Ross, Sharona B.
Financial implications of developing a hepatopancreaticobiliary (HPB) center have not been considered. We undertook this study to determine hospital income associated with a new HPB center and to gauge the opportunity cost associated with such a center. Operations included were based on the HPB fellowship curriculum and the six most commonly undertaken general surgery operations. The income with "core" HPB operations (n = 93) and the six most frequently undertaken general surgery operations (n = 583) at one hospital from June 2012 to June 2013 were determined. Patients were not screened based on the ability to pay. Data are reported as mean ± standard deviation. Per operation, hospital income with HPB operations and general surgery operations were 15, 583.20 ± 45, 909.41 and 5, 162.22 ± 33, 679.10 ( P < 0.005), respectively. Accordingly, net incomes of 1, 449, 238.04 (n = 93) and 3, 009, 572.78 (n = 583) were observed. Although general surgery operations are ubiquitous, HPB centers are uncommonly pursued at most hospitals, in part due to the patient volumes necessary to meet the expertise required. A "core" HPB operation produces triple the net income of a general surgery operation. Accordingly, significant financial benefit is achievable with the development of an HPB center when adequate volume is realized.